Learning OpenGL ES for iOS : a hands-on guide to modern 3d graphics programming - Buck, Erik M. (Addison-Wesley learning series., 2012)
Get Started Fast with Modern OpenGL ES Graphics Programming for iPhone, iPod touch, and iPad OpenGL ES technology underlies the user interface and graphical capabilities of Apple's iPhone, iPod touch, and iPad–as well as devices ranging from video-game consoles and aircraft-cockpit displays to non-Apple smartphones. In this friendly, thorough introduction, Erik M. Buck shows how to make the most of Open GL ES in Apple's iOS environment. This highly anticipated title focuses on modern, efficient approaches that use the newest versions of OpenGL ES, helping you avoid the irrelevant, obsolete, and misleading techniques that litter the Internet. Buck embraces Objective-C and Cocoa Touch, showing how to leverage Apple's powerful, elegant GLKit framework to maximize your productivity, achieve tight platform integration, and deliver exceptionally polished apps. If you've written C or C++ code and know object-oriented programming basics, this title brings together everything you need to fully master OpenGL ES graphics for iOS–including downloadable examples specifically designed to jumpstart your own projects. Coverage includes • Understanding core OpenGL ES computer graphics concepts and iOS graphics architecture • Integrating Cocoa Touch with OpenGL ES to leverage the power of Apple's platform • Creating textures from start to finish: opacity, blending, multi-texturing, and compression • Simulating ambient, diffuse, and specular light • Using transformations to render 3D geometric objects from any point of view • Animating scenes by controlling time through application logic • Partitioning data to draw expansive outdoor scenes with rolling terrain • Detecting and handling user interaction with 3D geometry • Implementing special effects ranging from skyboxes to particles and billboards • Systematically optimizing graphics performance • Understanding the essential linear algebra concepts used in computer graphics • Designing and constructing a complete simulation that incorporates everything you've learned.